Alfalfa Powder: Healthy Food Supplement for Sustainable Consumption - Pocol, Cristina-Bianca; Moldovan-Teselios, Călin; Pop, Ioana-Delia; Stan, Laura (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
An upward trend for plant dietary supplements has been reported lately in the Romanian market, suggesting that they could become a component of a sustainable food diet for consumers. The aim of this study was (1) to explore consumers’ perceptions about alfalfa powder (a plant dietary supplement), to identify their needs and expectations regarding the use of this product and to define the consumer profile; (2) to outline the significant factors of alfalfa sustainable consumption. For this purpose, the evaluation was performed using a questionnaire on a sample of consumers from two important Transylvanian cities (Deva and Cluj-Napoca). The results of the study indicate that the product is consumed by youth, adults and elderly people with upper-class education and high incomes. Emphasis was placed on identifying the main benefits perceived by the use of alfalfa powder. Hence, these are directly related to immunity (10%), detoxification (15%) and healthy dietary supplements (32%). Furthermore, since sustainability is a key factor for increasing quality of life, evidence emerged revealing alfalfa sustainable consumption. Consequently, this study shows that a more sustainable consumption of alfalfa can be stimulated through successful strategies for consumer education through label information including traceability data.